1994
DOI: 10.1128/iai.62.3.1046-1051.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing, and expression of the Escherichia coli cytolethal distending toxin genes

Abstract: A limited number of Escherichia coli isolates which produce an apparently novel toxin, termed cytolethal distending toxin (CDT), have been reported. The toxic activity produced by these strains causes certain cultured cell lines to become slowly distended and then disintegrate. DNA was isolated from the CDTproducing E. coli strain, 9142-88, and cloned into a cosmid vector. Plasmid DNA from a toxin-positive transductant was further subcloned until a plasmid with a 4-kb insert which still encoded the toxin activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
107
0
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(112 citation statements)
references
References 20 publications
2
107
0
1
Order By: Relevance
“…All the existing 11 PCR systems report high specificity and accuracy for typing of cdt genes, but have not been used widely for epidemiological studies in different regions (Pickett et al 1994;Clark et al 2002;Pandey et al 2003;Toth et al 2003;Bielaszewska et al 2004). Using the multiplex PCR system developed by Toth et al (2003) we have shown that it is sensitive and specific for detection of all different cdt genes, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the existing 11 PCR systems report high specificity and accuracy for typing of cdt genes, but have not been used widely for epidemiological studies in different regions (Pickett et al 1994;Clark et al 2002;Pandey et al 2003;Toth et al 2003;Bielaszewska et al 2004). Using the multiplex PCR system developed by Toth et al (2003) we have shown that it is sensitive and specific for detection of all different cdt genes, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The Cdt A and Cdt C polypeptides constitute the heterodimeric subunit (Lara-Tejero and Galan 2001; Lee et al 2003) that is required for CDT binding to target cells. Five different E. coli cdt sequences have been reported, cdt-I (Scott and Kaper 1994), cdt-II (Pickett et al 1994), cdt-III (Peres et al 1997), cdt-IV (Toth et al 2003) and cdt-V (Bielaszewska et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As indicated by Shenker et ai, the N-terminal sequence of A. actinomycetemcomitans CdtB is Asn-Leu-Ser-Asp-Phe-Lys-Val-Ala-Thr-Trp-Asn-Leu-Gln-Gly-Ser (21). No N-terminal sequence of the CdtA protein from any bacterium has been determined but a mature CdtA is suggested to be a lipoprotein (26) with the cysteine residue at position + I (corresponding to Cys-16 of CdtA in A. actinomycetemcomitans) as a Nterminal residue (II,14,15,24). A molecular mass of the A. actinomycetemcomitans CdtA from Cys-16 to Asn-222 is calculated as 22.9 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, COT was discovered in Escherichia coli OI28:H-as a novel cell distending and cytolethal toxin (8). The cdtABC genes encoding COT were first identified in E. coli OI28:H-and 086:H34 (15,19). Successively, the cdtABC gene homologs have been identified in Shigella dysenteriae (12), Campylobacter jejuni Abbreviations: CBD, chitin binding domain; COT, cytolethal distending toxin; OTT, dithiothreitol; GST, glutathione S-transferase; UP, localized juvenile periodontitis; NiH-SFF, Ni H_ chelated Sepharose Fast Flow.…”
mentioning
confidence: 99%
See 1 more Smart Citation